Interaction of rock-bolt supports while weak rock reinforcing by means of injection rock bolts - Krykovskyi, Oleksandr; Krykovska, Viktoriia; Skipochka, Serhii (Dnipro University of Technology, 2021)
Purpose is to analyze changes in shape and dimensions of a rock mass area, fortified with the help of a polymer, depending upon the density of injection rock bolts as well as the value of initial permeability of enclosing rocks to substantiate optimum process solutions to support roofs within the unstable rocks and protect mine workings against water inflow and gas emission. Methods. Numerical modeling method for coupled processes of rock mass strain and filtration of liquid components of a polymer has been applied. The model is based upon fundamental ideas of mechanics of solids and filtration theory. The problem has been solved using a finite element method. Its solution took into consideration both the initial permeability and the permeability stipulated by mine working driving, injection time of reagents and their polymerization, and effect of polymer foaming in the process of mixing of its components. Changes in physicomechanical and filtration characteristics of rock mass during polymer hardening were simulated. It has been taken into consideration that a metal delivery pipe starts operating as a reinforcing support element only after the polymer hardening. Findings. If three and five injection rock bolts are installed within a mine working section then stresses, permeability coefficients, pressure of liquid polymeric composition, and geometry of the fortified area of rock mass have been calculated. It has been shown that rock bolt location is quite important to form a rock-bolt arch. It has been demonstrated for the assumed conditions that if five injection rock bolts are installed within the mine working roof then close interaction between rockbolt supports takes place; moreover, the integral arch is formed within the mine working roof. Originality. Dependence of change in the polymer reinforced area upon a value of initial permeability of enclosing rocks has been derived. It has been shown that in terms of low values of initial permeability, geometry of rock-bolt supports as well as its size is identified only by means of a value of the unloaded zone around the mine working. In this context, initial permeability increase results in the enlarged diameter of the reinforced rock mass area in the neighbourhood of the injection rock bolt. Practical implications. The findings are recommended to be applied while improving a method to support the mine working roof and decrease water inflow as well as gas emission from the rocks, being undermined, into the working.

Мета. Дослідити зміни форми і розмірів зміцненої полімером області масиву залежно від щільності установки ін’єкційних анкерів і величини початкової проникності порід, що вміщують виробку, для обґрунтування оптимальних технологічних рішень з підтримки покрівлі в нестійких породах і захисту виробок від водоприпливу та газовиділення. Методика. У роботі використано метод чисельного моделювання зв’язаних процесів деформування породного масиву і фільтрації рідких компонентів полімеру. Основу моделі складають фундаментальні положення механіки твердого тіла та теорії фільтрації. Задача розв’язана із застосуванням методу скінченних елементів. При вирішенні враховувалася початкова проникність і проникність, обумовлена проведенням виробки, час нагнітання реагентів та їх полімеризації, ефект спінювання полімеру при змішуванні його компонентів. Моделювалася зміна фізико-механічних і фільтраційних властивостей породного масиву при застиганні полімеру. Враховувалося, що металева нагнітальна трубка вступає в роботу в якості армуючого елемента кріплення тільки після застигання полімеру. Результати. Для випадків установки в перерізі виробки трьох і п’яти ін’єкційних анкерів виконано розрахунок напружень, коефіцієнтів проникності, тиску рідкого полімерного складу, геометрії зміцненої області породного масиву. Показано, що схема розташування анкерів відіграє важливу роль у формуванні породно-анкерного перекриття. Для прийнятих в задачі умов показано, що при установці в покрівлі виробки п’яти ін’єкційних анкерів породно-анкерні опори тісно взаємодіють між собою, а в покрівлі гірничої виробки формується цілісне перекриття. Наукова новизна. Отримано залежність зміни площі зміцненої полімером області від величини початкової проникності порід, що вміщають виробку. Показано, що при низьких значеннях початкової проникності розміри і форма породно-анкерних опор визначаються тільки величиною розвантаженої зони навколо виробки, при цьому зростання початкової проникності призводить до збільшення діаметра зміцненої області масиву навколо ін'єкційного анкера. Практична значимість. Результати рекомендується використовувати при вдосконаленні технології підтримки покрівлі гірничих виробок з метою підвищення їх стійкості, зниження водоприпривів і газовиділення з підроблених порід у виробку.

Цель. Исследовать изменениие формы и размеров упрочненной полимером области массива в зависимости от плотности установки инъекционных анкеров и величины начальной проницаемости вмещающих пород для обоснования оптимальных технологи-ческих решений по поддержанию кровли в неустойчивых породах и защиты выработок от водопритоков и газовыделений. Методика. В работе использован метод численного моделирования связанных процессов деформирования породного массива и фильтрации жидких компонентов полимера. Основу модели составляют фундаментальные положения механики твердого тела и теории фильтрации. Задача решена с применением метода конечных элементов. При решении учитывалась начальная проницаемость и проницаемость, обусловленная проведением выработки, время нагнетания реагентов и их полимеризации, эффект вспенивания полимера при смешивании его компонент. Моделировалось изменение физико-механических и фильтрационных свойств породного массива при застывании полимера. Учитывалось, что металлическая нагнетательная трубка вступает в работу в качестве армирующего элемента крепи только после застывания полимера. Результаты. Для случаев установки в сечении выработки трех и пяти инъекционных анкеров выполнен расчет напряжений, коэффициентов проницаемости, давления жидкого полимерного состава, геометрии упрочненной области породного массива. Показано, что схема расположения анкеров играет важную роль в формировании породно-анкерного перекрытия. Для принятых в зада-че условий показано, что при установке в кровле выработки пяти инъекционных анкеров породно-анкерные опоры тесно взаимодействуют между собой, а в кровле горной выработки формируется целостное перекрытие. Научная новизна. Получена зависимость изменения площади упрочненной полимером области от величины начальной проницаемости вмещающих пород. Показано, что при низких значениях начальной проницаемости размеры и форма породно-анкерных опор определяются только величиной разгруженной зоны вокруг выработки, при этом рост начальной проницаемости приводит к увеличению диаметра упрочненной области массива вокруг инъекционного анкера. Практическая значимость. Результаты рекомендуется использовать при совершенствовании технологии поддержания кровли горных выработок с целью повышения их устойчивости, снижения водопритоков и газовыделения из подрабатываемых пород в выработку.
Keywords: support; mine working; rock bolt; geomechanical parameters; filtration parameters; modeling